Behavior problems in adolescence and subsequent mental health in early adulthood: results from the World Trade Center Health Registry Cohort. (August 2018) - Gargano, Lisa; Locke, Sean; Li, Jiehui; Farfel, Mark
Abstract Background The present study examined the association between 9/11-related adolescent behavioral problems on mental health outcomes in early adulthood. Methods Data from enrollees of the World Trade Center Health Registry, who completed at least one adolescent (2006–2007 or 2011–2012) and adult survey (2011–2012 or 2015–2016), were analyzed. Adolescent behavioral difficulties were assessed using the adolescent-reported Strengths and Difficulties Questionnaire (SDQ). Adult mental health outcomes included binge drinking, smoking status history, 9/11-related post-traumatic stress disorder (PTSD), depression, and the self-reported number of physician mental health diagnoses. Multivariable regression was used to estimate associations of SDQ scores with mental health outcomes. Results Of the 297 enrollees, 16.8% (n = 50) had abnormal/borderline SDQ scores as an adolescent. Binge drinking was not associated with adolescent SDQ scores. Enrollees with abnormal/borderline SDQ scores as an adolescent were more likely to be a consistent smoker (odds ratio (OR): 5.6, 95% confidence interval (CI): 1.2–25.2), have probable PTSD (OR: 3.5, 95% CI: 1.3–9.8), depression (OR: 6.2, 95% CI: 2.7–13.9), and to have two or more self-reported physician-diagnosed mental health conditions as an adult (OR 5.6, 95% CI: 2.0–12.5). Conclusions The findings of this study underscore the need to intervene early with children exposed to traumatic events so as to avert later adolescent and adult problem behaviors.